2008
DOI: 10.1111/j.1440-1754.2008.01352.x
|View full text |Cite
|
Sign up to set email alerts
|

Discussing withholding and withdrawing of life‐sustaining medical treatment in paediatric inpatients: Audit of current practice

Abstract: The majority of inpatient deaths at The Royal Children's Hospital occur in acute circumstances and involve patients with chronic conditions. In most cases, death follows WWLSMT. Discussions with families are documented as first occurring relatively late in the course of the final admission although opportunities for earlier discussions may exist. Further research is needed to understand more about how and when discussions actually take place, what the barriers to communication are and to what extent opportunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
35
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 25 publications
3
35
1
1
Order By: Relevance
“…A variety of studies over the last two decades have highlighted the intensive care setting as the central, and in some instances nearly exclusive, place for making life and death decisions within a modern children's hospital [1-5]. Although physician, nursing, ethical and legal aspects have since been important foci of research in this difficult-to-study area [6,7], scant information exists about the time-course of the process of withdrawal of life-sustaining treatment from the moment of discussion to actual death.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of studies over the last two decades have highlighted the intensive care setting as the central, and in some instances nearly exclusive, place for making life and death decisions within a modern children's hospital [1-5]. Although physician, nursing, ethical and legal aspects have since been important foci of research in this difficult-to-study area [6,7], scant information exists about the time-course of the process of withdrawal of life-sustaining treatment from the moment of discussion to actual death.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Research from Australia, 4,5,9 the United States, 10,11 and the United Kingdom 1 has found that children most frequently die as a result of withdrawal of life support, whereas studies from Brazil, 3 France, and Eastern and Central Europe 2 identify that most children die in PICUs as a result of failed cardiopulmonary resuscitation. Some have argued that this can be attributed largely to cultural differences related to end-oflife care practices and the social acceptance of the death of a child.…”
mentioning
confidence: 99%
“…Those 2 singleinstitution studies showed limitation of support for 74% and 84% of pediatric deaths. 15,16 The scarcity of literature from the United States in the previous decade and the overall paucity of pediatric multiinstitutional studies led us to examine the patterns of pediatric deaths and end-of-life care in PICU settings in a multiinstitutional cohort from across the country. Are we still limiting support in just more than one-third of pediatric deaths, as shown in 16 US PICUs in 1994, or are we closer to the numbers reported recently from Australia?…”
mentioning
confidence: 99%
“…Are we still limiting support in just more than one-third of pediatric deaths, as shown in 16 US PICUs in 1994, or are we closer to the numbers reported recently from Australia? 7,15,16 We aimed specifically to understand how frequently limitations of support occurred at the end of life in PICU settings in the United States and sought to identify variations in end-oflife practices related to specific PICU and patient variables.…”
mentioning
confidence: 99%